A catalogue of Indian Pyraloidea (Lepidoptera) - Singh, Navneet; Ranjan, Rahul; Talukdar, Avishek; Joshi, Rahul; Kirti, Jagbir Singh; Chandra, Kailash; Mally, Richard (Zootaxa, 2022)
We catalogue 1,695 Indian Pyraloidea species in 509 genera. Of these, Pyralidae comprises 518 species in 182 genera, which represents 8.35% of the global Pyralidae diversity of 6,197 species. Crambidae are represented by 1,177 species in 327 genera, accounting for 11.29% of the global Crambidae diversity of 10,418 species. Botys medullalis Snellen, distributed in Indonesia, is reinstated to species status as Sciorista medullalis (Snellen), stat. rev., comb. nov. Sylepta [sic] picalis Hampson, 1903, syn. nov. is synonymised with Syllepte picalis Hampson, 1899. A replacement name Archernis polynesiae N. Singh & Mally, nom. nov. is proposed for Archernis fulvalis Hampson, 1913a, a junior homonym of Archernis fulvalis Hampson, 1899e. We review the chronology and quantity of species descriptions of Indian Pyraloidea by various authors. Summaries of all subfamilies of Pyralidae and Crambidae present in India provide information on adult and larval morphology, food plant associations, and diversity and distribution in major biogeographic zones of India.